2020
DOI: 10.1186/s12920-020-0698-x
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA and messenger RNA abnormalities in pediatric sepsis: a preliminary study

Abstract: Background: Sepsis represents a complex disease with dysregulated inflammatory response and high mortality rate. Long noncoding RNAs (lncRNAs) have been reported to play regulatory roles in a variety of biological processes. However, studies evaluating the function of lncRNAs in pediatric sepsis are scarce, and current knowledge of the role of lncRNAs in pediatric sepsis is still limited. The present study explored the expression patterns of both lncRNAs and mRNAs between pediatric sepsis patients and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Likewise, high lncRNA NEAT1 expression showed close correlation with increased disease risk, enhanced severity, and higher 28-day mortality in sepsis (Yang et al, 2020). Bai et al (Bai et al, 2020) also identified four pediatric sepsisassociated lncRNAs, including RP11-1220 K2.2.1-7, ANXA3-2, TRAPPC5-1, and ZNF638-1. These lncRNAs were significantly highly expressed in septic children and could be novel biomarkers for pediatric sepsis.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Likewise, high lncRNA NEAT1 expression showed close correlation with increased disease risk, enhanced severity, and higher 28-day mortality in sepsis (Yang et al, 2020). Bai et al (Bai et al, 2020) also identified four pediatric sepsisassociated lncRNAs, including RP11-1220 K2.2.1-7, ANXA3-2, TRAPPC5-1, and ZNF638-1. These lncRNAs were significantly highly expressed in septic children and could be novel biomarkers for pediatric sepsis.…”
Section: Introductionmentioning
confidence: 80%
“…Of these, 1,146 lncRNAs were specifically detected in sepsis groups, suggesting that lncRNAs were globally activated in sepsis samples. Previous studies have suggested that lncRNAs may be potential biomarkers for prognosis of sepsis, such as lncRNAs MALAT1, NEAT1, RP11-1220 K2.2.1-7, ANXA3-2, TRAPPC5-1, and ZNF638-1 (Chen et al, 2018a;Geng et al, 2019;Bai et al, 2020), which have been introduced in introduction. Herein, the PCA result showed sepsis and control specimens could be separated by the second component, providing the solid evidence that lncRNAs could be diagnostic biomarkers to distinguish sepsis from no_sepsis and control specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Wang et al reported that miR-15a/16 was up-regulated in serum of patients with neonatal sepsis; investigations into its mechanism revealed that lncRNA SHNG16 could act as a ceRNA and positively regulate TLR4 by competitively binding miR-15a/16 in LPS-induced macrophages, thus indicating that lncRNA SNHG16 affected inflammatory responses in neonatal sepsis (Wang et al, 2018). Apart from neonatal sepsis, Bai et al reported a total of 1,488 DE lncRNAs and 1,460 DE mRNAs between ten pediatric patients with sepsis and twelve healthy controls; they conducted a co-expression network analysis of the DE lncRNAs and mRNAs, suggesting a correlation between lncRNA and mRNA expression that were involved in the pathogenesis of sepsis (Bai et al, 2020). Considering the different pathophysiological processes between children and adult sepsis (Weiss et al, 2020), further research is needed to elucidate the roles of lncRNAs and explore their molecular mechanisms in children with sepsis.…”
Section: Lncrnas In Children With Sepsismentioning
confidence: 99%
“…Apart from neonatal sepsis, Bai et al. reported a total of 1,488 DE lncRNAs and 1,460 DE mRNAs between ten pediatric patients with sepsis and twelve healthy controls; they conducted a co-expression network analysis of the DE lncRNAs and mRNAs, suggesting a correlation between lncRNA and mRNA expression that were involved in the pathogenesis of sepsis ( Bai et al., 2020 ). Considering the different pathophysiological processes between children and adult sepsis ( Weiss et al., 2020 ), further research is needed to elucidate the roles of lncRNAs and explore their molecular mechanisms in children with sepsis.…”
Section: Role Of Lncrnas In Sepsismentioning
confidence: 99%